A HIDDEN MARKOV MODEL: DEPENDENCIES BETWEEN RANDOM VARIABLES AND ITS REPRESENTATION - SETIAWATY, B. (MILANG Journal of Mathematics and Its Applications, 2002)
This article shows the nature of dependencies between random variables in a hidden Markov model. Using these properties,we will show that the law of a hidden Markov model is completely speciﬁed by a set of four parameters which is called a representation of the hidden Markov model.